Evaluation of Corrosion Condition of Some Steel-Reinforced Concrete Infrastructures Available In Pokhara Valley of Nepal - Laudari, Ishwor; Phulara, Nav Raj; Gautam, Madhab; Bhattarai, Jagadeesh (Tribhuvan University Journal, 2021)
Assessment of the corrosion condition of different types of eighty steel-reinforced concrete (SRC) structures of Pokhara Valley (Nepal) was carried out in the present study using a half-cell potential measurement (HCPM) method without destruction of specimens. It is concluded from the experimental results that the SRC structures found at dried places in Pokhara areas showed a low percentage(i.e., < 10%) of corrosion risk, while the fencing pillars used for decoration as well as boundary purposes, and the sewer pipes at damp places found under the high percentage (i.e., > 90%) of corrosion risk. The SRC infrastructures, which have rough and cracked surfaces with high humid surrounding environments, are at high risk of corrosion. The SRC columns of the buildings in Pokhara Valley are at a slightly higher corrosion risk than the SRC roof structures.